Local Capital Scarcity and Small Firm Growth: Evidence from Real Estate Booms in China - Harald Hau; Difei Ouyang (Center for Economic Studies and ifo Institute (CESifo), 2019)
In geographically segmented credit markets, local real estate booms can deteriorate the funding conditions for small manufacturing firms and undermine their competitiveness. Using exogenous variation in the administrative land supply across 172 Chinese cities, we show that higher predicted real estate prices cause higher borrowing costs for small manufacturing firms, reduce their bank lending, lower their investment rate and labor productivity, and reduce their output and TFP growth by economically significant magnitudes. These effects are absent in large and listed companies with access to the national capital market. The evidence highlights the benefits of financial market integration.
Keywords: D22; D24; R31; 330; factor price externalities; real estate booms; firm growth; financial constraints